PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS JASA PELAYANAN KONSUMEN PADA PDAM TIRTANADI CABANG SUNGGAL - MEDAN - Andini Pratiwi Siregar; Tan Kamelo; Dedi Harianto; Suhaidi Suhaidi (Universitas Sumatera Utara, 2017)
ABSTRACT One of the common services that are profitable is Drinking of Water Company (PDAM/PAM) despite the profit,the company taps country like it is advantageous people.The goalwas focused more on the bussiness prosperty of the people,this has been done considering the importance of drinking water for human life.It is enshrined in the provisions of Article 33 paragraph (3) of the 1945 Constitution which reads,earth and water and natural resources contained in it are comtrolled by the state and used for the people’s welfare. The result of research and discussion describes setting up the legal relationship between consumers and service user of drinking water by the Regional Water Company Tirtanadi Sunggal Medan Branch outlined in the agreement in the form standard agreements or standards.The agreement contains the identify of the parties,the rights and obligations of both parties,Prohibition and sanctions given to constumers,termination and dispute resolution.PDAM legal accountability Tirtanadi Sunggal Medan Branch related to violation of consumer rights of service user of drinking water is responsibility of the rise in civil case of default or tort where taps can be subjek to payment of compensation.In addition to the civil responsibility taps are also subjeck criminal liability if the breach consumers rights was indetified as a criminal act.Form of consumer legal protection of drinking water service user in case of violation of consumer right so consumers can be use the provision stipulated in Law No .8 of 1999 on the protection of the lawsuit .While law suit to bussiness that taps cam be charged through a civil ,criminal and administrative state. Key word: Accountabiility Law,Consumer ,Service